Implementing Professional Midwife-Led Maternity Care in India for Healthy Pregnant Women: A Community Case Study - Beckingham, Andy; Downe, Soo; Fernandez, Evita; Reed, Becky; Kaur, Indie; Aziz, Nuzhat; Kingdon, Carol (Frontiers in Public Health, 2022)
More women and neonates die each year in India than in almost every other country of the world. Since 1947, India has in principle provided free medical maternal health care to all pregnant and childbearing women. Although rates of maternal and neonatal deaths have fallen since the 1990s, major inequalities remain. Some Indian States have very high rates of interventions, (e.g., cesarean section), while others have intervention and care rates that are too low. Disrespectful treatment of women in labor and lack of evidence-based practice have also been reported. The World Health Organization and others have strongly recommended that professional midwives (trained in a woman-centered philosophy and to international standards) have a key role for reducing mortality and morbidity, minimizing unnecessary interventions in pregnancy and labor, and improving maternal care quality in low- and medium-income countries. This paper provides a community case-report of the first professional midwifery programme in India designed to international standards, implemented in 2011 in Hyderabad. We describe the design and implementation in the programme's first eleven years, as a basis for further scale-up and testing in India, and in other low- or medium-income countries. The ultimate aim is to improve maternal care quality, choice and outcomes in India and in similar socio-economic and cultural settings.